2019
DOI: 10.1136/bmjoq-2018-000544
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction model for 30-day acute readmissions among older medical patients: the influence of social factors along with other patient-specific and organisational factors

Abstract: BackgroundReadmission rate is one way to measure quality of care for older patients. Knowledge is sparse on how different social factors can contribute to predict readmission. We aimed to develop and internally validate a comprehensive model for prediction of acute 30-day readmission among older medical patients using various social factors along with demographic, organisational and health-related factors.MethodsWe performed an observational prospective study based on a group of 770 medical patients aged 65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 46 publications
2
27
0
1
Order By: Relevance
“…Another indicator of effective service delivery is readmission rate, as patients returning to the hospital apply additional pressure to the health care system by increasing patient volume 37 . Our study con rmed the previous ndings of no effect of models of consultant-led ED services on readmission rates 19,20 and the readmission rate which was found is similar to the one found at another Danish Acute Hospital 38 . These ndings are in contrast to a British study that found a signi cant decrease in readmission within 28 days of discharge utilising adjusted analyses 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Another indicator of effective service delivery is readmission rate, as patients returning to the hospital apply additional pressure to the health care system by increasing patient volume 37 . Our study con rmed the previous ndings of no effect of models of consultant-led ED services on readmission rates 19,20 and the readmission rate which was found is similar to the one found at another Danish Acute Hospital 38 . These ndings are in contrast to a British study that found a signi cant decrease in readmission within 28 days of discharge utilising adjusted analyses 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Physical, psychological and social characteristics associated with higher risks of adverse discharge outcomes were selected based on past studies [6][7][8][9][10][11][12][13][14]:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, past studies suggested that some physical, psychological and social characteristics increased the risk of these adverse discharge outcomes in older patients [6,7]. In particular, difficulty to walk, comorbidities, cognitive impairment, living alone and lack of social support have been identified as strong predictors of readmissions within 30 days post-discharge [8][9][10][11][12][13][14]. While not all readmissions are avoidable, a large proportion (27-76%) is thought to be preventable if best-practice discharge preparation and practices are followed [15].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of mortality and readmission predictive models focus on maximizing performance of the models rather than real-world impact on care delivery. In doing so, model developers may use predictors that require data collection from additional workflows [ 5 6 ], use variables that may not be fully available or have to mature during the hospitalization [ 6 9 ], or may not integrate the model into their electronic health record (EHR) either for real-time prospective validation or for calculation to support clinical workflows [ 6 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current predictive models are frequently focused on highly specific segments of the population, such as the elderly [ 13 14 ], or on specific disease states, such as pneumonia [ 11 , 15 ], chronic obstructive pulmonary disease[ 16 , 17 ] or heart failure [ 11 , 18 21 ]. While this approach can lead to improved model performance, it tends to cover only a subset of the population, and may not fully recognize that complex patients have multiple, often related, diagnoses that are together driving their clinical risk.…”
Section: Introductionmentioning
confidence: 99%